Attitudes to ageing: an overview of Australian perspectives of health support systems for the older person. (August 2020) - Jeyasingam, Neil
Objectives: Older adults utilise health care systems to a higher frequency than younger groups, and are more vulnerable to system bias regarding ageing and expectations of old age. This narrative review attempts to outline the available literature regarding how various health support systems perceive the older adult, with an Australian focus. Conclusions: Perspectives on ageing are generally negative regardless of health industry. Possible contributors to this include elements of death anxiety, inadequate education and inadequate occupational exposure during training.